Synthesis, characterization and thermal behaviour of solid state compounds of 4-methylbenzylidenepyruvate with lighter trivalent lanthanides - Marques, R. N.; Melios, C. B.; Ionashiro, Massao [UNESP] (Elsevier B.V., 2002)
Solid state Ln-4-Me-BP compounds, where Ln stands for lighter trivalent lanthanides (lanthanum to europium) and 4-Me-BP is 4-methylbenzylidenepyruvate, have been synthesized. Elemental analysis, complexometry, X-ray powder diffractometry, infrared spectroscopy and simultaneous thermogravimetry-differential thermal analysis (TG-DTA), have been used to characterize and to study the thermal behaviour of these compounds. The results provided information concerning the stoichiometry, crystallinity, thermal stability and thermal decomposition. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: lighter trivalent lanthanides; 4-methylbenzylidenepyruvate; characterization; thermal behaviour